2011
DOI: 10.1182/blood.v118.21.2064.2064
|View full text |Cite
|
Sign up to set email alerts
|

A Nationwide Prospective Multicenter Study of Clinical Features and Outcomes of Non-Hodgkin Lymphoma in Thailand: An Analysis of 939 Cases

Abstract: 2064 OBJECTIVE: Non-Hodgkin lymphoma (NHL) is the most common hematologic malignancy in Thailand. The objective of the study was to evaluate clinical features, histopathology, treatment outcomes and prognostic factors in Thai adult patients with NHL. METHODS: Using web-based registry system, we prospectively collected clinical information of newly diagnosed NHL patients from eleven major medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, these laboratory features could be indirectly implied by illnesses composing in CCI. Although, we did not have dedicated comprehensive central pathology review for all cases in this study which might affect the distribution of pathologic subtypes, we previously reported high concordance (94%) between diagnoses reported in our registry and diagnoses in randomly selected cases reviewed by pathology [24]. The age cutoff at 75 years old was somewhat arbitrary but this cutoff was partly referred to approximated life expectancy of Thai population in general by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these laboratory features could be indirectly implied by illnesses composing in CCI. Although, we did not have dedicated comprehensive central pathology review for all cases in this study which might affect the distribution of pathologic subtypes, we previously reported high concordance (94%) between diagnoses reported in our registry and diagnoses in randomly selected cases reviewed by pathology [24]. The age cutoff at 75 years old was somewhat arbitrary but this cutoff was partly referred to approximated life expectancy of Thai population in general by the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…Thai lymphoma study group (TLSG) is a multi-institutional collaborative panel of hematologists and hemato-pathologists from 13 major medical centers in Thailand. The detailed information of TLSG was described previously elsewhere [9,10]. The registry prospectively included newly diagnosed lymphoma patients aged older than 15 years old from all participating centers since September 2006.…”
Section: Methodsmentioning
confidence: 99%
“…More than 200 cases were reported in literature but less than 20 cases in Asia [2] . In Thailand, only 3 HSTCL cases (less than 1%) were reported from the cohort of 1983 lymphoma patients from Siriraj Hospital [3] and none from the 939 lymphoma patients was reported by the Thai Lymphoma Study Group during 2007 and 2009 [4] . HSTCL is usually composed of medium-sized lymphoid cells with marked sinusoidal infiltration of spleen, liver and bone marrow [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B - cell lymphoma (DLBCL) is the most common aggressive B-cell non-Hodgkin lymphoma (NHL), accounting for 65% of NHL in Thailand. 1 It is a heterogeneous disease classified as germinal center-like B-cell (GCB) and non-germinal B-cell subtypes that arise from different cells of origin (COO). Hans algorithm including CD10, BCL6, and MUM1 protein expressions are used for the classification of COO of DLBCL, and the common methods for determining the COO are immunohistochemistry (IHC) and gene expression profiling (GEP).…”
Section: Introductionmentioning
confidence: 99%